2014
DOI: 10.17305/bjbms.2014.4.35
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insulin like growth factor-1 in development of coronary artery ectasia

Abstract: Coronary artery ectasia (CAE) is characterized by inappropriate dilatation of the coronary vasculature. The mechanisms of CAE are not well known. Insulin-like growth factor-1 (IGF-1) may make endothelial cells and smooth muscle cells more sensitive to the effects of growth hormone. In the present study, we hypothesized that IGF-1 may have an impact on the formation of ectasia and aneurysm in arterial system, and aimed to investigate the associations between the presence of CAE and serum IGF-1 levels in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
1
0
1
Order By: Relevance
“…In one study, a reduced level of Vitamin D was shown to be associated with CAE [ 5 ]. However, exaggerated inflammation, as seen in the form of either the human immunodeficiency virus (HIV) infection alone [ 6 ] or higher levels of uric acid (UA) and high sensitivity CRP (Hs-CRP) [ 7 ], elevated monocytes to high-density lipoprotein ratio (MHR) [ 8 ], a high neutrophil to lymphocyte (N/L) ratio [ 9 ], elevated insulin-like growth factor I (IGF-I) level [ 10 ], or high levels of inflammatory cytokines (i.e., IL-1b, tumor necrosis factor alpha (TNF-α), and interleukin 10 (IL-10) [ 11 ]), has been the main inciting factor in CAE development and progression. CAE often presents as exercise-induced angina; however, it is not uncommon to present as ACS as well [ 12 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, a reduced level of Vitamin D was shown to be associated with CAE [ 5 ]. However, exaggerated inflammation, as seen in the form of either the human immunodeficiency virus (HIV) infection alone [ 6 ] or higher levels of uric acid (UA) and high sensitivity CRP (Hs-CRP) [ 7 ], elevated monocytes to high-density lipoprotein ratio (MHR) [ 8 ], a high neutrophil to lymphocyte (N/L) ratio [ 9 ], elevated insulin-like growth factor I (IGF-I) level [ 10 ], or high levels of inflammatory cytokines (i.e., IL-1b, tumor necrosis factor alpha (TNF-α), and interleukin 10 (IL-10) [ 11 ]), has been the main inciting factor in CAE development and progression. CAE often presents as exercise-induced angina; however, it is not uncommon to present as ACS as well [ 12 - 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Концентрація ІФР-1 в стінці аневризм знижується, що вказує на потенційну роль цього чинника у механізмах регулювання метаболізму цього білка [26,27]. Інший можливий механізм формування аневризм і ектазій артерій -підвищена чутливість ендотеліальних і гладеньком'язових клітин до дії ГР під впливом ІФР-1 [28].…”
Section: вступunclassified